Pengaruh Likuiditas Dan Modal Kerja Terhadap Return on Equity (Pada Perusahaan Sub Sektor Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia Tahun 2018-2020) - Purnamasari, Atika (JOURNAL INTELEKTUAL, 2022)
Introduction/Main Objectives: To determine the effect of liquidity and working capital on profitability in food and beverage sub-sector companies listed on the Indonesia stock exchange in 2018-2020. Background Problems: The empirical condition of the profitability of food and beverage companies as measured using return on equity (ROE) in the last 3 years has fluctuated. Novelty: Decision Analysis to invest in the company's working capital and be able to manage its receivables correctly by using the right calculation. Research Methods: sampling technique used purposive sampling and obtained 18 companies, with analysis of the data used the computer Statistical Program for Social Science (SPSS). Finding/Results: The size of the company's liquidity will not affect the return on equity of the food and beverage sector companies and the number of products sold will also be greater, which will then be followed by the greater the profit the company will earn. Conclusion: The liquidity variable has no effect on return on equity, while working capital partially has a significant effect on return on equity.